Brain-Derived Neurotrophic Factor in Chronic Periodontitis - Jôice Dias Corrêa; Daniele Sirineu Pereira; Mila Fernandes Moreira Madeira; Celso Martins Queiroz-Junior; Danielle Glória Souza; Mauro Martins Teixeira; José Eustáquio Costa; Antônio Lúcio Teixeira; Tarcília Aparecida da Silva (Mediators of Inflammation)
Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophic factor family. Outside the nervous system, BDNF has been shown to be expressed in various nonneural tissues, such as periodontal ligament, dental pulp, and odontoblasts. Although a role for BDNF in periodontal regeneration has been suggested, a function for BDNF in periodontal disease has not yet been studied. The aim of this study was to analyze the BDNF levels in periodontal tissues of patients with chronic periodontitis (CP) and periodontally healthy controls (HC). All subjects were genotyped for the rs4923463 and rs6265 BDNF polymorphisms. Periodontal tissues were collected for ELISA, myeloperoxidase (MPO), and microscopic analysis from 28 CP patients and 29 HC subjects. BDNF levels were increased in CP patients compared to HC subjects. A negative correlation was observed when analyzing concentration of BDNF and IL-10 in inflamed periodontium. No differences in frequencies of BDNF genotypes between CP and HC subjects were observed. However, BDNF genotype GG was associated with increased levels of BDNF, TNF-α, and CXCL10 in CP patients. In conclusion, BDNF seems to be associated with periodontal disease process, but the specific role of BDNF still needs to be clarified.